2017
DOI: 10.1186/s12864-017-3630-9
|View full text |Cite
|
Sign up to set email alerts
|

Interferon signaling in ascites-associated macrophages is linked to a favorable clinical outcome in a subgroup of ovarian carcinoma patients

Abstract: BackgroundAlthough tumor-associated macrophages (TAMs) are essential for cancer progression, connections between different clinical outcomes and transcriptional networks have not been reported. We have addressed this issue by analyzing global expression patterns of TAMs isolated from the ascites of ovarian cancer patients.ResultsTAMs isolated from different ovarian cancer patients can be stratified by coexpression or principal component analysis into subgroups with specific biological features and associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 58 publications
3
48
0
Order By: Relevance
“…Among these, three proteins are migration-promoting candidates as suggested by literature data [28][29][30] , i.e., TGFBI, TNC, and FN1 (Table 1). A similar observation was made for macrophage mannose receptor 1 (MRC1, CD206) and scavenger receptor cysteine-rich type 1 protein (CD163), which are known to be commonly upregulated in TAM and alternatively activated macrophages 8,17,25 , and thus serve as plausibility controls.…”
Section: Comparative Secretome Analysis Of Mdm Subtypes Identifies Casupporting
confidence: 61%
See 1 more Smart Citation
“…Among these, three proteins are migration-promoting candidates as suggested by literature data [28][29][30] , i.e., TGFBI, TNC, and FN1 (Table 1). A similar observation was made for macrophage mannose receptor 1 (MRC1, CD206) and scavenger receptor cysteine-rich type 1 protein (CD163), which are known to be commonly upregulated in TAM and alternatively activated macrophages 8,17,25 , and thus serve as plausibility controls.…”
Section: Comparative Secretome Analysis Of Mdm Subtypes Identifies Casupporting
confidence: 61%
“…TAMs constitute a prominent cell population in ascites known to promote tumor growth, metastasis, and immunosuppression [14][15][16] . TAMs are reprogrammed by factors of the TME to adopt a pro-tumorigenic and immunosuppressive phenotype, which is linked to a poor clinical outcome 8,13,17,18 . TAMs contribute to the tumor secretome by releasing a plethora of soluble mediators, such as interleukin (IL)-6, IL-10, C-C chemokine motif ligand 18 (CCL18), CCL22, tumor necrosis factor α, and transforming growth factor beta (TGFβ), that trigger protumorigenic signaling pathways in both tumor and host cells of the TME [19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Malignant ascites often contain a large number of TAMs, which are correlated with poor prognosis in ovarian cancer patients. 8,27 However, the mechanism by which TAMs accumulate in the tumor microenvironment remains unclear. In the present study, we found that high levels of POSTN existed in malignant ascites and were correlated with CD163 + TAMs.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, a group of patients, characterised by upregulation of gene expression of IFN-gamma, showed a longer survival. High IFN-gamma levels, in fact, affect (abrogate-block) IL-12 inhibition by malignant ascites, with a favourable outcome 14. It has been shown that by combining the surgical state and the IL-17 and IL-21 levels in the ascitic fluid, a risk score for predicting the outcome of the patient may be obtained 15.…”
Section: Discussionmentioning
confidence: 99%